Return on Assets, Firm Value, and Good Corporate Governance: Empirical at Foreign Exchange Banks In Indonesia - Ningsih, Risna; Nirwanto, Nazief; Zuhroh, Diana (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2020)
Every firm tries to improve the performance in order to achieve its goal, namely maximizing the firm wealth or value (Salvatore, 2005). The purpose of this study was to examine the effect of Return on Assets on firm value with Good Corporate Governance as its moderating variable. This study used 29 Foreign Exchange Banks in LQ45 category and listed in Indonesia Stock Exchange in 2014-2017. The firm value was measured by using Tobin's Q while GCG was measured by Independent commissioner. The results of the study showed thatÂ Good corporate governance which is proxied by the independent commissioner weakens the influence of Return on Assets to the firm value.